A preliminary concrete mix design for SCC with marble powders - Alyamac, Kuersat Esat; Ince, Ragip (Elsevier Sci Ltd, 2009)
The marble has been commonly used as a building material since ancient times. Disposal of the waste materials of the marble industry, consisting of very fine powders, is one of the environmental problems worldwide today. However, these waste materials can be successfully and economically utilized to improve some properties of fresh and hardened self-compacting concrete (SCC). The aim of this study is to find some relationship between properties of the fresh SCC and the hardened SCC containing marble powder. For this purpose, the mix design approach based on monogram developed by Monteiro and co-workers for normal vibrated concrete was adapted to SCC mixes. In order to obtain this monogram, a series of SCC mixes with different water/cement ratios and water/powder ratios were prepared. Several tests such as slump-flow. T-500 time, L-box, V-funnel and sieve segregation resistance were applied for fresh concrete and tests such as compressive strength and split-tension strength at 7, 28 and 90 days were performed for hardened concrete. In conclusion, the mix design method based on monogram can be suggested for preliminary design in SCC. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Self-compacting concrete; Marble powder; Waste; Strength